Application of Discovery Learning Model to Improve Critical Thinking Ability of Class 5 IPA - Sri Rahayu (Universitas Sebelas Maret, 2020)
This type of research is classroom action research. The purpose of this study was to improve critical thinking skills in science by applying the Discovery Learning model. The results showed that the application of the Discovery Learning model can improve critical thinking skills in science. The percentage of critical thinking skills in the very good, good, adequate, and poor categories. In pre-cycle it was 41%, cycle I was 68%, increased in cycle II to 86%, and increased again in cycle III was 95%.